Concurrent Control of Position/Orientation of a Redundant Manipulator based on Virtual Spring-Damper Hypothesis - Kim, Sung-Kyun; Bae, Ji-Hun; Oh, Yonghwan; Oh, Sang-Rok (2011 IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION (ICRA), 2011)
Redundant manipulator control usually brings about a lot of complexity. This paper proposes a quite simple approach for concurrent set-point regulation of position and orientation of a redundant manipulator using the virtual spring-damper hypothesis, which offers human-like movements without solving the inverse dynamics. For orientation, quaternion representation is applied to give singularity-free orientation control. Augmenting quaternion feedback to the state vector of the system, the stability is analytically proved, and dynamic simulation is conducted for validation of the method. Competition between position and orientation control is also briefly discussed based on the simulation results.